A construção do espaço em D. Aquino Corrêa, Silva Freire e Manoel de Barros : imaginário e pós-colonialismo - Amorim, Moisés Carlos de (2020)
This research aims to investigate, in the light of the theory of Imaginary and Postcolonialism, the process of building regional space in the works of D. Aquino Corrêa, Silva Freire and Manoel de Barros. Each author, representative and active in his generation, configures an artistic language, which recreates myths through primal images (JUNG, 2012c), in which the space is poetically reconstructed, consolidating regional traits. In addition, such myths configure values that reflect on the modern colonial world-system, aiming to build a preliminary thinking (MIGNOLO, 2002), which goes beyond the coloniality of power stage. Since the emergence of the regionalist conception in the beginning of the 20th century in Mato Grosso, with D. Aquino Corrêa, there has been a concern with the local identity, interweaving in the literary work a set of important elements, such as: nature, conquerors, cuisine, people, cultures, etc., in short, all the surrounding reality that populates the imaginary of art. In the analysis of the poetic worldview of the three authors mentioned, the theory of imaginary and critical thinking of post-colonialism is used to understand the myths that encompass the particularities of each work and the process by which has become a recurring experience in the cosmicized space, the relationship with the regional identity, as well as with the conception of space, which in the poetry of D. Aquino is an image of paradise (colonized by the pioneers in the period of territorial expansion); in Silva Freire, archetype of the “Great Mother” (caregiver of the people in their daily invention of life); and, in Manoel de Barros' writing, it becomes a gulliverized symbol (the miniaturized nature as opposed to the centers of capitalist power), whose dialectic highlights the relations between the local and the world; in each author, a mythical aura of historical knowledge, the lived daily life and the relationship between man and space was elaborated.